Contestations over urban space: exploring the discourse and dynamics between residents in Hermanus, Zwelihle and Dubai in a post-protest environment - Van der Westhuizen, Nicola (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.